Bank Misconduct, Board Diversity and CEO Turnover - Casu, B.; Gallo, A.; Kalotychou, Elena; Sarkisyan, A. (My University, 2023)
This paper investigates corporate reactions to bank misconduct episodes. We test whether more diverse boards have a stronger disciplining effect and trigger “changes at the top”. We consider misconduct fines issued by US regulators to EU listed banks during the period 2009–2018. We find that CEO dismissals are more likely following regulatory fines, but not during the investigation process. Board gender diversity does not seem to impact on boards’ decision to fire the CEO, nor reinforce boards’ disciplining effect in the presence of misconduct. The presence of foreign directors and age diversity increase the likelihood of CEO dismissal following regulatory sanctions.
Keywords: Board of directors; Bank; Misconduct; Gender diversity; CEO turnover